Τhe relationship between human resource empowerment and business performance in Greek fitness clubs - Βαμβουκάκη, Μαρία Ειρήνη (Πανεπιστήμιο Πελοποννήσου, 2013)
The primary purposes of this study were: (a) to determine the extent to which the human resource empowerment is being used in Greek fitness clubs and (b) to examine the relationship between human resource empowerment and the selected variables: (a) business performance (profit, ROI, sales volume and market share), (b) managers’ educational background (c) managers’ position of responsibility, and (d) managers’ gender in the fitness clubs. The Questionnaire developed Vogt & Murrell (1990), focused on the issue of empowerment, was modified and simplified by Kriemadis (2011) and Papaioannou (2011). The modified questionnaire consisted of 30 questions related to empowerment, demographic characteristics of the respondents and their managers’ perceptions related to the performance of the fitness club. All 250 «big» Greek fitness clubs, which had at least four managers, were surveyed. Responses were received from 187 Greek fitness clubs for a response rate of 73.5 percent. The findings of this study were as follows: 1. Human Resource Empowerment process is applied to a mediocre extent by Greek fitness clubs, as sixty percent of Greek Fitness Clubs were using the “empowerment style” of management. 2. There was a strong and positive relationship between the level of human resource empowerment and business performance of fitness clubs. 3. The levels of human resource empowerment were related to managers’ educational background. 4. The levels of human resource empowerment were related to managers’ position of responsibility. 5. The levels of human resource empowerment were related to managers’ gender.
Η σχέση της ενδυνάμωσης ανθρώπινου δυναμικού και της επιχειρησιακής επίδοσης σε Ελληνικά γυμναστήρια
Keywords: Επιλογή προσωπικού; Human resource empowerment; Βusiness performance; Fitness clubs; Sport organizations